2014
DOI: 10.12691/education-2-4-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Pre-Service Science Teachers’ Self-Efficacy Beliefs of Teaching in Kenya and the United States of America; USA

Abstract: This study examined and compared science teacher efficacy beliefs of elementary pre-service teachers in Kenya and U.S.A. by surveying 168 Kenyan and 189 US Pre-service teachers through a cross-sectional survey research design. Data were collected using STEBI-B scale, an inventory developed by by Enochs and Riggs (1990), with a reported Cronbach's Alpha coefficients as 0.90 and 0.76 for Personal Science Teacher Efficacy (PSTE) and Science Teacher Outcome Expectancy (STOE), respectively. Data were analysed both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…However, there are few studies in the literature where different results are obtained from the results of this study. For example, Aurah and McConnell [15] found that gender had no effect on the personal science-teaching efficacy of male and female science teachers.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few studies in the literature where different results are obtained from the results of this study. For example, Aurah and McConnell [15] found that gender had no effect on the personal science-teaching efficacy of male and female science teachers.…”
Section: Discussionmentioning
confidence: 99%
“…The literature review did not reveal a significant number of recent studies investigating teachers' self-efficacy in teaching biological concepts. In fact, most of the studies focus on pre-service teachers, measure their self-efficacy in Science using STEBI B (Avery & Meyer, 2012;Aurah & McConnell, 2014, Aydin & Boz, 2010Bayraktar 2011;Bergman & Μorphew, 2015;Bursal, 2012;Gray, 2017;Hechter, 2011;Norris, Morris & Lummis, 2018). Specifically, Avery and Meyer (2012) refer that the inquiry-based science courses correlate positively with pre-service teachers' science self-efficacy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This review defines teacher self-efficacy as a teacher's conviction or beliefs about his or her own capabilities to organize and accomplish instructional tasks (Bandura, 1997). The definition covers operationalized constructs that measure personal teaching efficacy (Gibson & Dembo, 1984), teaching efficacy belief (van Acker, 2013), and self-efficacy in specific teaching tasks, including student engagement, classroom management, instructional strategies (Tschannen-Moran & Hoy, 2001), science teaching efficacy beliefs (Riggs & Enochs, 1990), and inclusive instructions (Sharma, Loreman, & Forlin, 2012). Mastery experience, on the other hand, refers to teachers' personalized professional success or failure experiences.…”
Section: Criteria For Inclusion Of Studiesmentioning
confidence: 99%